Healthcare-associated infections in the first four years of a pediatric surgical intensive care unit - Atıcı, Serkan; Kılıç, Sinan; Karadeniz Cerit, Kıvılcım; Kıyan, Gürsu; Soysal, Ahmet (The Journal of Infection in Developing Countries, 2025)
Introduction: Healthcare-associated infections (HAIs) are a significant cause of morbidity and mortality, particularly among critical pediatric surgical patients. This study aimed to evaluate the incidence, distribution, types, and pathogens involved in HAIs, in a newly established pediatric surgery intensive care unit (PSICU). Methodology: The Infection Control Team of Marmara University Pendik Training and Research Hospital identified and documented HAI cases according to the Centers for Disease Control and Prevention criteria over a four-year period following the unit's opening. Prospective, laboratory-based surveillance of HAIs was conducted within the PSICU from 1 January 2011 to 30 November 2014. Continuous monitoring and early detection of HAIs are crucial for implementing timely and effective infection control measures. Results: A total of 599 patients were admitted to the PSICU, and 90 HAI cases were identified, resulting in an overall HAI rate of 15%. The incidence density was 14.7 per 1,000 patient-days. The most prevalent types were bloodstream infections (40%), pneumonia (23.4%), and urinary tract infections (17.8%). The primary pathogens were Klebsiella spp. (27.8%), Acinetobacter baumannii (13.9%), Staphylococcus spp. (13.9%), and Candida spp. (13.9%). Conclusions: There is limited data on HAI rates in PSICUs, and this study showed that infection rates in the PSICU were not higher than in pediatric intensive care units and neonatal intensive care units. The incidence of HAIs in this study was not higher than reports from other PSICUs in developing countries like Mexico, Brazil, and Egypt; but was higher compared to the rates reported in developed countries such as the US.